IMPACT OF INDUSTRY TYPE, COMPANY SIZE, PROFITABILITY AND LEVERAGE TO CARBON EMISSION DISCLOSURE - Murwanto, Haris; Trilestari, Rr. Dian Indriana (International Journal of Social and Management Studies, 2022)
The aim of this study is to analyze the impact of industry type, company size, profitability, and leverage to carbon emission disclosure empirically. The population in this research are all mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample used were 14 companies with an observation period of 2018-2020, so 42 company data were obtained. This research used legitimacy theory and stakeholder theory. The sample selection method in this research used purposive sampling with quantitative approaches. The analytical technique used in hypothesis testing is multiple linear regression analysis. The results of this research indicate that company size affects carbon emission disclosure. Meanwhile, the profitability, and leverage do not affect carbon emission disclosure. The limitations of this research are: (1) The measurement index of the company’s carbon emission disclosure coverage is not following the conditions of companies in Indonesia, (2) Eliminating 1 variable, namely industry type. The future research agendas are: (1) Further research is expected to improve the list of carbon emission disclosure items, (2) Further research is expected to be able to develop measurements for carbon emission disclosure that are following conditions in Indonesia. Keywords: Carbon Emission Disclosure, Industry Type, Company Size, Profitability, Leverage